PENGARUH INTELLECTUAL CAPITAL TERHADAP KINERJA PERUSAHAAN ASURANSI DI INDONESIA - Lestari, Henny Setyo (Jurnal Manajemen, 2017)
The purpose of this paper is to analyze the role of intellectual capital (IC) and its relationship with financial performance of Indonesian Insurance during the period 2003-2012. In total, 11 insurance companies were selected as the sample. Regression model (partial least squares) has been applied to examine the relationship between IC and companies return on assets ratio (ROA). The results of the research revealed that Value added capital coefficient (VACA) have a significantly negative effect and value added human capital (VAHU) has a positive significant effect on the performance of the company (ROA), while the value added of structural capital (SCVA), firm size and financial leverage does not have a significant effect on company performance (ROA). Value added human capital (VAHU) and financial leverage has a positive significant effect on the performance of the company (ROE), while the Value Added Capital Coefficient (VACA), Value Added Structural Capital (SCVA) and firm size has no significant effect on company performance (ROE).